The great saphenous vein-an anatomical study. - Hosapatna M; D Souza AS; Sriprajna; Kotian SR (Department of Surgery, UKM Medical Centre, 2014)
The anatomical variations are more frequently encountered in the venous system particularly in the superficial veins when compared to the arterial system. The great saphenous vein is the longest vein of the body and represents pre-axial vein of lower limb. The venous anatomy is of great importance to the surgeons and sonographers. The present study included 25 lower limbs during routine dissection for undergraduate students in the Department of Anatomy, Kasturba Medical College, Manipal, India. We studied the great saphenous vein with reference to its formation, relation with the medial malleolus, distance from patella, level of termination and variation in its major tributaries. The findings were recorded, tabulated and photographed. Aforementioned anatomical facts including mode of termination of great saphenous vein can be important for surgeons planning intervention in this area. This vein is used as an arterial graft because of the marked anatomical remodeling. Thus, a good understanding of the typical ultrasound appearance of the great saphenous vein, its relationship to the major bony landmarks is significant.